Flavonoids and fractions from Saccharum officinarum L. juice: antinociceptive agents and molecular docking evaluations with µ-opioid receptor. Issue 4 (16th February 2023) - Gomes, Anne Katherine C.; Alves Soares, Mariana; Miranda, Ana Luísa P.; Tributino, Jorge Luiz Mendonça; Goetze Fiorot, Rodolfo; Kuster, Ricardo Machado; Gomes, Anne Caroline C.; Simas, Naomi Kato
Abstract: Opioid receptors mediate antinociceptive effects. Methanolic fractions from sugarcane varieties (MFSCf) were evaluated in classic nociception models. Interactions between bioactive compounds and the µ-opioid receptor (µOR) through docking analysis were also studied. Five methanolic fractions of sugarcane juice were obtained and analysed by LC-ESI-MS/MS. The fractions and standards of phenolic compounds were evaluated in a nociception model using the formalin test. All MFSCfs exhibited antinociceptive activity in the first phase of the formalin test. Docking analyses corroborates with the in vivo test results, suggesting that the phenolic substances are able to activate µOR. These results, for the first time, implicate phenolic constituents from sugarcane juice and other phenolic compounds in the activation of µOR. The antinociceptive activity of fractions from sugarcane juice suggests the potential pharmacological use of this species, widely cultivated in Brazil. Graphical Abstract: UF0001